2007
DOI: 10.1002/mrm.21178
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral tissue characterization in a RIF‐1 tumor model: Monitoring the ADC and T2 responses to single‐dose radiotherapy. Part II

Abstract: A multispectral (MS) approach that combines apparent diffusion coefficient (ADC) and T 2 parameter maps with k-means (KM) clustering was employed to distinguish multiple compartments within viable tumor tissue (V1 and V2) and necrosis (N1 and N2) following single-dose (1000 cGy) radiotherapy in a radiation-induced fibrosarcoma (RIF-1) tumor model. The contributions of cell kill and tumor growth kinetics to the radiotherapy-induced response were investigated. A larger pretreatment V1 volume was correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
4
31
0
Order By: Relevance
“…Benign liver lesions including cysts and hemangiomas demonstrate increased apparent diffusion coefficient (ADC) values compared to malignant lesions including HCC and metastases (1921). Quantitative DWI measurements (22) and combined multi-parametric (ADC + T2 + proton density) MRI measurements (2325) have demonstrated the potential to differentiate intratumoral tissue types as well as characterize therapy response.…”
Section: Introductionmentioning
confidence: 99%
“…Benign liver lesions including cysts and hemangiomas demonstrate increased apparent diffusion coefficient (ADC) values compared to malignant lesions including HCC and metastases (1921). Quantitative DWI measurements (22) and combined multi-parametric (ADC + T2 + proton density) MRI measurements (2325) have demonstrated the potential to differentiate intratumoral tissue types as well as characterize therapy response.…”
Section: Introductionmentioning
confidence: 99%
“…[139][140][141] This leads to stochastic and cyclical changes in blood flow 142 that, in turn, have profound effects on the local environmental properties, and the resulting evolutionary selection pressure applied to cancer cells. [147][148][149][150] In fact, intratumoral spatial heterogeneity has been associated with resistance to therapy, 151 tumor growth, 152 and poor prognosis, 153 and therefore has direct clinical consequences. [143][144][145][146] Thus, these subregions, or habitats, are expected to contain cells with similar genotypes and phenotypes, including those that confer therapy resistance.…”
Section: Habitat Imagingmentioning
confidence: 99%
“…151,181,182 Preclinical studies are valuable because these habitats can be identified by coregistration with histology. 151,181,182 Preclinical studies are valuable because these habitats can be identified by coregistration with histology.…”
Section: Habitat Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Henning et al . (Henning et al , 2007) applied k-means clustering to the ADC and T 2 data of RIF-1 mouse tumors treated with single-dose radiotherapy (1000 cGy). Four clusters were identified: two viable clusters (oxygenated and hypoxic) and two necrotic clusters (cellular and acellular).…”
Section: 0 Diffusion-weighted Mri (Dwi)mentioning
confidence: 99%